Thinking with Nancy Fraser in understanding the impact of online learning and support during the Covid19 pandemic. (Journal of Student Affairs in Africa, 2022)
The Covid-19 pandemic has changed the face of Higher Education Institutions (HEI) in profound ways.  Since 2020 HEI’s have been forced to think creatively and quickly about how to respond to arising challenges of completing the academic year and ensuring throughput and retention of students.  Historically Disadvantaged Institutions (HDIs) have been hard hit in respect of resources and the under-preparedness of the student cohort who are attracted to HDIs to take on the challenge of online learning.   This article uses mixed methods approach, which includes survey data to measure service delivery and an auto-ethnographic approach using the observations and reflections of the author to discuss the impact of online learning and support during the Covid-19 pandemic.   Utilizing Nancy Fraser’s model of social justice, which focuses on the concept of participatory parity the paper will using the economic and cultural dimension provide an understanding of the constraints and enablements that impacted student’s ability to access online learning and support.
Keywords: social justice; participatory parity; academic and psycho-social support